The influence of atoms of second coordination sphere on phonon dispersion of diamond - V. A. Sachkov (Омский научный вестник)
Within the framework of the phenomenological model of twoparticle interaction, the effect of the interaction energy of atoms from the second coordination sphere on the phonon dispersion is considered. This approach makes it possible to vary the growth of the phonon frequency relative to the optical phonon in the center of the Brillun zone. The effects of the contribution to the Raman spectra from longitudinal optical phonons with frequencies higher than their frequency at the center of the Brillouin zone are discussed. The contribution to the frequency of interaction of atoms from the second coordination sphere for some phonons is obtained in an explicit form. The formulas obtained will be useful for calculating the spectra of Raman scattering of light by optical phonons localized in diamond nanocrystals.